A leverage-based model of speculative bubbles - Gadi Barlevy (Federal Reserve Bank of Chicago, 2011)
This paper examines whether theoretical models of bubbles based on the notion that the price of an asset can deviate from its fundamental value are useful for understanding phenomena that are often described as bubbles, and which are distinguished by other features such as large and rapid booms and busts in asset prices together with high turnover in asset ownership. In particular, I focus on riskshifting models similar to those developed in Allen and Gorton (1993) and Allen and Gale (2000). I show that such models could explain these phenomena, and discuss under what conditions booms and speculative trading would emerge. In addition, I show that these models imply that speculative bubbles can be associated with low rather than high premia on loans, in accordance with observations on credit conditions during episodes in which asset prices boomed and crashed.
Keywords: 330